The Impact of Digitalization on Employee Well-being in Nordic Multinational Corporations - Rusanen, Lisa Marie (My University, 2026)
Digitalization has significantly changed the nature of work itself in multinational corporations (MNCs), especially in the Nordic countries, where flexible working practices and advanced digital infrastructure are widely used. The adoption of digital technology has been a significant benefit for organizations, as it opens many new ways to operate in order to succeed. However, these technologies also have negative aspects, especially their impact on employee well-being. This thesis examines the relationship between digitalization, employee well-being, and the role of digitalized work demands and resources in employee well-being in Nordic multinational companies. The study was conducted using a qualitative research method. The empirical data for the study were collected through nine semi-structured interviews with employees working in Nordic multinational corporations. The data were analyzed using thematic analysis, and the Job Demands–Resources (JD-R) model was used as the theoretical framework for the analysis. Research shows that digitalization increases work demands, for example through constant online presence, information overload, faster work pace and blurring of boundaries between work and leisure. An increased cognitive load on the employee may lead to decreased ability for the employee to focus and recover. However, at the same time, digital transformation provides important resources for work such as flexibility, autonomy, digital collaboration tools, social and leadership support, and learning and developing skills. These work resources can increase employee motivation, create a better balance between work and life, and help employees manage the pressures of digital work. Research results suggest that the impact of digitalization on employee well-being is not simply positive or negative but depends on the balance between demands and resources. In multinational companies operating in the Nordic countries, factors such as trust-based leadership, low hierarchy and employee autonomy influence how digital work is experienced. The study complements existing literature by highlighting the duality and context-dependence of digital work and by extending the JD-R model to better describe digitally mediated work environments.

Digitalisaatio on muuttanut merkittävästi työn luonnetta monikansallisissa yrityksissä, etenkin Pohjoismaissa, joissa joustavat työtavat ja edistyksellinen digitaalinen infrastruktuuri ovat laajasti käytössä. Digitaalisen teknologian käyttöönotto on ollut merkittävä etu organisaatioille, sillä se avaa monia uusia toimintatapoja menestymisen saavuttamiseksi. Näillä teknologioilla on kuitenkin myös negatiivisia puolia, erityisesti työntekijöiden hyvinvoinnin näkökulmasta. Tässä tutkimuksessa tarkastellaan, miten digitalisaatio vaikuttaa työntekijöiden hyvinvointiin pohjoismaisissa monikansallisissa yrityksissä sekä millainen rooli digitaalisilla työvaatimuksilla ja -resursseilla on tämän suhteen muotoutumisessa. Tutkimus toteutettiin laadullisella tutkimusmenetelmällä. Tutkimuksen aineisto kerättiin yhdeksän puolistrukturoidun haastattelun avulla, joiden haastateltavat olivat pohjoismaisissa monikansallisissa yrityksissä työskenteleviä henkilöitä. Aineisto analysoitiin temaattisen analyysin avulla. Tutkimustulosten tarkastelussa käytettiin tutkimuksen teoreettista viitekehystä, johon hyödynnettiin työn vaatimusten ja voimavarojen (Job Demands-Resources) mallia. Tutkimustulokset viittaavat siihen, että digitalisaatio lisää työn vaatimuksia esimerkiksi jatkuvan verkossa olemisen, tietotulvan, nopeamman työtahdin sekä työn ja vapaa-ajan rajojen hämärtymisen kautta. Työntekijän kognitiivisen kuormituksen lisääntyminen voi heikentää keskittymis- ja palautumiskykyä. Samanaikaisesti digitaalinen muutos tarjoaa myös tärkeitä työresursseja, kuten joustavuutta, itsenäisyyttä, digitaalisia yhteistyövälineitä, sosiaalista ja johtajuustukea sekä oppimista ja osaamisen kehittämistä. Nämä työresurssit voivat lisätä työntekijöiden motivaatiota, luoda paremman tasapainon työn ja yksityiselämän välille sekä auttaa työntekijöitä selviytymään digitaalisen työn paineista. Tutkimustulokset osoittavat, että digitalisaation vaikutus työntekijöiden hyvinvointiin ei ole yksiselitteisesti vain positiivinen tai negatiivinen, vaan se riippuu työn vaatimusten ja resurssien välisestä tasapainosta. Pohjoismaissa toimivissa monikansallisissa yrityksissä tekijät kuten luottamukseen perustuva johtaminen, matala hierarkia ja työntekijöiden autonomia vaikuttavat siihen, miten itse digitaalinen työ koetaan. Tutkimus täydentää aiempaa kirjallisuutta tuomalla esiin digitaalisen työn kaksinaisuutta ja kontekstiriippuvuutta, sekä laajentamalla JD-R-mallia siten, että se soveltuu paremmin digitaalisten työympäristöjen tarkasteluun.
Keywords: well-being at work; employees; digitalisation; international corporations; human resource management; Nordic countries; leadership (activity); autonomy (cognition); work satisfaction; enterprises; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business